Identification and Analysis of Mechanical Properties of Composite Materials for Pipe Hanger Application - Geetha, V.; Meenadevi, R.; Marshiana, D. (International Journal of Engineering and Technology, 2018)
In this paper an innovative material was developed to overcome the high wear rate originated in slide bearing material (SBM). It is reviewed from various literatures that many nearby industries like Power Plants and Oil & Gas Factories uses this type of SBM. The material used in the preparation of SBM is pure Polyterafluoroethylene (PTFE) which has a property of self lubrication and lower friction coefficient instead of hardness and high coefficient of friction. The high wear rate obtained from the PTFE can be condensed by integration of appropriate glass and bronze filler materials. The property of varying load (VL), sliding distance (SD), sliding velocity (SV) and filler content in Polyterafluoroethylene are experimentally tested for the development of new object. A relative analysis based on the properties of four different composites for the improvement of PTFE by the addition of filler content.1) PTFE, (PTFE + 15 % Glass Filler + 20 % Glass Filler + 30% Glass Filler and 40% Glass Filler etc.)2) PTFE, (PTFE + 15 % Bronze Filler + 20 % Bronzes Filler + 30% Bronze Filler and 40% Bronze Filler etc...)Taguchi technique is used for the preparation of experimental chart and the data collected after the experimental results were setup in Annova Table. Co-efficient of friction and Hardness is robustly subjective due to composition of filler material content. The results were tabulated to find the material having the superior wear performance.Â Â
Keywords: PTFE; Composite material; hardness; tensile strength